Influence of Disease Process and Duration on Acute Phase Proteins in Serum and Peritoneal Fluid of Horses with Colic. (29th January 2015) - Pihl, T.H.; Scheepers, E.; Sanz, M.; Goddard, A.; Page, P.; Toft, N.; Andersen, P.H.; Jacobsen, S.
Abstract : Background: The acute phase proteins (APP) serum amyloid A (SAA), haptoglobin, and fibrinogen are valuable blood biomarkers in equine inflammatory diseases, but knowledge of factors influencing their concentrations in blood and peritoneal fluid (PF) of horses with colic is needed. Objectives: The objective of this study was to investigate the influence of demographics (age, sex, breed), disease process (simple obstruction, strangulating obstruction, inflammatory), disease location, disease duration, hypovolemia, and admission hospital on concentrations of APP, lactate and white blood cell counts (WBC) in horses with colic admitted to 2 referral hospitals. Animals: The study included 367 horses with colic admitted at 2 referral hospitals. Methods: Prospective multicenter observational study of clinical data, as well as blood and PF biomarkers. Associations between biomarker concentrations and clinical variables were analyzed using multivariate linear regression analysis. Results: Increasing pre‐admission duration of colic was associated with increased concentrations of APP in blood and PF. Blood concentrations of SAA and fibrinogen were associated with disease process (inflammatory, strangulations, simple obstructions) in more colic duration groups (5–12 and >24 hours) than any of the other biomarkers. No relevant associations between demographic factors, hospital, or hydration status and the measured biomarkers were found. Conclusions and Clinical Importance: In horses with colic, concentrations of APP are associated mainly with disease process and duration of colic and may thus be used for assessment of disease independently of demographic or geographic factors. Serum amyloid A may be a diagnostic marker for use in colic differential diagnosis, but further evaluation is needed.